1997
DOI: 10.1046/j.1365-3040.1997.d01-15.x
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of leaf surface wetness for montane and subalpine plants

Abstract: The frequency and duration of water on leaf surfaces have important consequences for plant growth and photosynthetic gas exchange. The objective of the present study was to compare the frequency and duration of leaf wetness under natural field conditions among species and to identify variation in structural features of leaves that may reduce surface wetness. During June-Septemher 1992 in the central Rocky Mountains (USA), natural leaf wetting due to rain and dewfall was observed on 79 of 89 nights in open mead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
150
0
4

Year Published

1999
1999
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 169 publications
(162 citation statements)
references
References 54 publications
8
150
0
4
Order By: Relevance
“…The adaxial and abaxial holm oak leaf side performed differently in terms of wettability (Table I), as previously found for other plant species (Brewer and Smith, 1997;Fernández et al, 2014). We showed that the hydrophobic character of the abaxial leaf side is clearly associated with the roughness provided by the high density, chemical composition, and structure of trichomes.…”
Section: Trichome Chemical Composition and Structuresupporting
confidence: 84%
See 3 more Smart Citations
“…The adaxial and abaxial holm oak leaf side performed differently in terms of wettability (Table I), as previously found for other plant species (Brewer and Smith, 1997;Fernández et al, 2014). We showed that the hydrophobic character of the abaxial leaf side is clearly associated with the roughness provided by the high density, chemical composition, and structure of trichomes.…”
Section: Trichome Chemical Composition and Structuresupporting
confidence: 84%
“…We showed that the hydrophobic character of the abaxial leaf side is clearly associated with the roughness provided by the high density, chemical composition, and structure of trichomes. According to the classification suggested by Brewer et al (1991) and Brewer and Smith (1997), the abaxial holm oak leaf trichomes may belong to the lifting strategy group, while further trials will require characterizing the performance of liquid water with the adaxial oak leaf side at a macroscopic level.…”
Section: Trichome Chemical Composition and Structurementioning
confidence: 99%
See 2 more Smart Citations
“…Our results with L. stoechas are in accordance with Garrat & Segal (1988), who reported that dew provides significant amounts of water especially relevant in water-stressed plants. Although water precipitated on the leaf surface causes an immediate depletion of leaf gas exchange (Smith & McClean, 1989 ;Ishibashi & Terashima, 1995 ;Brewer & Smith, 1997), once dew water is absorbed from the leaf surface, the photosynthetic performance of water-stressed plants can be improved through increased plant water status (Grammatikopoulos & Manetas, 1994 ;Munne! -Bosch & Alegre, 1999).…”
Section: mentioning
confidence: 99%